The search for atrial fibrillation and its impact on public health (Swiss Medical Weekly, 2017)
Atrial fibrillation may be clearly symptomatic and is easily amenable to state-of-the-art treatment, most importantly oral anticoagulation therapy for the prevention of thromboembolism. However, atrial fibrillation may also go unnoticed for long periods in many patients. This silent or subclinical atrial fibrillation is nevertheless associated with thromboembolic risk just like clinically evident atrial fibrillation. Early detection of atrial fibrillation in patients at increased thromboembolic risk and consequent oral anticoagulation therapy may have a significant impact on public health. This review focuses on screening recommendations for atrial fibrillation and on the impact of silent atrial fibrillation in various clinical scenarios.